A cross sectional study of knowledge, attitude and practices regarding rabies and its management among attendees of anti-rabies clinic of tertiary care hospital of central India - Jadhao, Ashok; Mamilwar, Monali (International Journal Of Community Medicine And Public Health, 2020)
Background: Rabies is a viral zoonotic disease which affects all warm-blooded animals. Human infection usually occurs following transdermal bite or scratch by infected animal. Rabies is fatal but preventable disease. Around the world, knowledge, attitude and practices studies about rabies have been widely used to understand disease and preventive measures. Methods: A cross-sectional study was conducted in the anti- rabies clinic of the tertiary care hospital of central India from January 2020 to March 2020. Data was collected using pre-designed, semi structured questionnaire from 424 participants. Descriptive statistics and chi square test were applied. Results: A total 424 attendees participated in our study. Mean age of participant was 35.94 (±15.3) years, 60.37% were male and 39.63% were female. Overall, 53.77% of participants had adequate knowledge and 60.38% had positive attitude and 68.63% had adopted adequate practices towards rabies. A significant association was found between knowledge score and age, gender, education and occupation. Attitude score was significantly associated with age, gender, occupation and education. A significant association was found between practice score and age, gender and education. Conclusions: The study showed that majority of participant had adequate knowledge, positive attitude and adopted appropriate practices about rabies. However there exists some knowledge gaps among participants on treatment and preventive measures. Their knowledge, attitude and practices with respect to prevention and management of rabies can be improved by providing proper health education.